Using RT-qPCR, Proteomics, and Microscopy to Unravel the Spatio-Temporal Expression and Subcellular Localization of Hordoindolines Across Development in Barley Endosperm - Shabrangy, Azita; Roustan, Valentin; Reipert, Siegfried; Weidinger, Marieluise; Roustan, Pierre-Jean; Stoger, Eva; Weckwerth, Wolfram; Ibl, Verena (Frontiers in Plant Science, 2018)
Hordeum vulgare (barley) hordoindolines (HINs), HINa, HINb1 and HINb2, are orthologous proteins of wheat puroindolines (PINs) that are small, basic, cysteine-rich seed-specific proteins and responsible for grain hardness. Grain hardness, is, next to its protein content, a major quality trait. In barley, HINb is most highly expressed in the mid-stage developed endosperm and is associated with both major endosperm texture and grain hardness. However, data required to understand the spatio-temporal dynamics of HIN transcripts and HIN protein regulation during grain filling processes are missing. Using reverse transcription quantitative PCR (RT-qPCR) and proteomics we analyzed HIN transcript and HIN protein abundance from whole seeds (WSs) at four ((6 days after pollination (dap), 10 dap, 12 dap and ≥ 20 dap)) as well as from aleurone, subaleurone and starchy endosperm at two (12 dap and ≥ 20 dap) developmental stages. At the WS level, results from RT-qPCR, proteomics and western blot showed a continuous increase of HIN transcript and HIN protein abundance across these four developmental stages. Miroscopic studies revealed HIN localization mainly at the vacuolar membrane in the aleurone, at protein bodies (PBs) in subaleurone and at the periphery of starch granules in the starchy endosperm. Laser microdissetion (LMD) proteomic analyses identified HINb2 as the most prominent HIN protein in starchy endosperm at ≥ 20 dap. Additionally, our quantification data revealed a poor correlation between transcript and protein levels of HINs in subaleurone during development. Here, we correlated data achieved by RT-qPCR, proteomics and microscopy that reveal different expression and localization pattern of HINs in each layer during barley endosperm development. This indicats a contribution of each tissue to the regulation of HINs during grain filling. The effect of the high protein abundance of HINs in the starchy endosperm and their localization at the periphery of starch granules at late development stages at the cereal-based end-product quality is discussed. Understanding the spatio-temporal regulated HINs is essential to improve barley quality traits for high end-product quality, as hard texture of the barley grain is regulated by the ratio between HINb/HINa.